Gifted child: psychological and pedagogical aspect of teacher kindergarten - Svitlana Chupakhina (Vasyl Stefanyk Precarpathian National University, 2017)
The paper analyzes the problems of identifying and training mathematically giftedpreschoolers. The need for training teachers to work with gifted children and creating specialconditions of mathematical and logical abilities of the child-oriented area of its shine. Key words: gift, mathematical capabilities, intellectually gifted child, awareness ofteacher.